FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI PASIEN MELAKUKAN PERAWATAN ORTODONTIK DI RSGMP PROF. SOEDOMO - , DEOZOLA REVICI R ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Orthodontic treatment is a treatment that aims to improve teeth arrangement neatly and orderly, and to improve the relation of occlusions between maxilla and mandible. Individual motivation in orthodontic treatment influenced by several factors, such as gender, age, education level, socioeconomical level, ethnic group and distance residence. This study aims to know what the most influencing factor to patient motivation of ortodontic treatment in RSGMP Prof. Soedomo. This study used the cross-sectional approach. The subjects of this study were 100 people, which patients were from age 16-25 years in orthodontic clinic RSGMP Prof. Soedomo. Motivation assessment of orthodontic treatment was tested by motivation questionnaire in modified Likert scale. Hypothetical measurement conducted using the simple linear regression and than continued with multiple regression with 95% level of confidence. The result of this study shows significant influence between ethnic group and education level with patient motivation of orthodontic treatment in RSGMP Prof. Soedomo (p=0,036 for gender) and (p=0,000 for ethnic group). The result analysis of multiple regression show after controlled by gender, only ethnic group that has influence significantly to motivation patient do orthodontic treatment in RSGMP Prof. Soedomo ( p = 0,000 . The value of R = 0,528 meaning ethnic group has a moderate degree of correlation with the motivation of patients to do orthodontic treatment in RSGMP Prof. Soedomo. In conclusion, ethnic group was the most influence factor to patient motivation of ortodontic treatment in RSGMP Prof. Soedomo. Java was the most ethnic group that seek orthodontic treatment in RSGMP Prof. Soedomo.